AB0472 PRIMARY SJOGREN SYNDROME ASSOCIATED INTERSTITIAL LUNG DISEASE: FEATURES, TREATMENT AND OUTCOME OF A MONOCENTRIC COHORT. (June 2019) - Manfredi, Andreina; Sebastiani, Marco; Vacchi, Caterina; Luppi, Fabrizio; Cerri, Stefania; Cassone, Giulia; Salvarani, Carlo
Abstract : Background: Primary Sjögren's syndrome (pSS) is an autoimmune systemic disease characterized by lymphocytic infiltration of exocrine glands, mainly resulting in dysfunction of salivary and lachrymal glands and symptomatic xerostomia and xerophthalmia. About one third of patients also present extra-glandular manifestations and, among them, interstitial lung disease (ILD) is one the most frequent, occurring in about 10– 20% of patients. ILD is associated with an impaired quality of life and physical capacity and to a reduced 10-year survival. Despite it seems to bemore frequently detected in late stages of thedisease, some authors suggest that ILD can be diagnosed before pSS in 20% of cases. Main predictive factors of progression of pSS-ILD have not been clearly investigated in previous studies and no evidence-based treatment is defined for these patients. Objectives: To describe the clinical and serologic features and the outcome of a monocentric cohort of pSS-ILD and the possible differences between patients treated or not with immunosuppressive treatment Methods: We retrospectively evaluated the 37 pSS-ILD patients followed at our Rheumatology Unit (male/female ratio 1/6.4, mean age 69.6±11.3 years, mean disease duration of pSS 5±5.2 years). Among them, 18 patients (48.6%; group 1) underwent immunosuppressive treatment because of lung disease, namely mycophenolate mofetil (9 patients, 50%), cyclophosphamide (3, 16.7%), azathioprine (5, 27.8%), high dose steroids (1, 5.6%), while 19 patients were not treated (group 2). Results: No significant differences were observed in regard of age, male/female ratio, and disease duration of ILD and pSS, while a significant difference was observed regarding the lung function of the 2 groups; the forced vital capacity (FVC) and the diffusion lung capacity of CO (DLCO) at baseline were significantly lower in the group 1 (FVC 78.6% vs 99.4% p=0.008; DLCO 45.7% vs 56.9%, p=0.025; in group 1 and group 2, respectively). No significant difference was observed between baseline and follow-up for FVC and DLCO in both groups, regardless the immunosuppressive drug (fig. 1 ). At the end of follow-up FVC increased, decreased and remained stable in 5.3/10.5/84.2% and 16.7/27.8/55.6%, in group 1 and group 2, respectively; DLCO increased, decreased and remained stable in 10.5/21.1/68.4% of group 1, while remained stable or decreased in 61.1 and 38.9 of treated patients, respectively (figure 1 ). Conclusion: At our knowledge, few studies have investigated the features of pSS-ILD and the role of immunosuppressive drugs in these patients. Our data suggest that the decline of lung function is one of the most significant parameters to guide the prescription of immunosuppressive drugs, but no differences can be observed according to the treatment in term of effectiveness. However, no studies have investigated the correctness of this approach or the efficacy of the MMF or CFX in pSS-ILD. Our study is strongly limited by the retrospective design and the low number of patients evaluated, but these data set attention on this unmet need. Further prospective studies are mandatory to clarify the impact of ILD in pSS patients and the correct therapeutic approach. References: [1] Baldini C, Pepe P, Quartuccio L, et al. Primary Sjogren's syndrome as a multi-organ disease: impact of the serological profile on the clinical presentation of the disease in a large cohort of Italian patients. Rheumatology. 2014; 53: 839-844 [2] Manfredi A, Sebastiani M, Cerri S, et al.Prevalence and characterization of non-sicca onset primary Sjögrensyndrome with interstitial lung involvement. Clin Rheumatol. 2017;36:1261-1268. Disclosure of Interests: None declared